Oral Health related treatment needs among Autistic Children: A Review - Agrawal, Amit; Mukul, Sailesh Kumar (Journal of Orofacial Research, 2017)
Autism is a neurodevelopment disorder allied with atypical brain constitution and function due to which communication, speech, behaviour, and cognitive functions weaken. Autism patients have many emotional, physical, health-related issues and oral health is one of them. As oral health is a wide range reflection of our general health, thus to achieve a good overall health focus on oral health is equally important. Every child has a unique characteristic, thus their emotional, physical and health needs are different. Therefore, the aim of this paper is to review and discuss the literature related to oral health characteristics and treatment needs of children with Autism Spectrum Disorder to facilitate the provision of care by dental practitioners.